Model Bimbingan Pendidikan Agama Islam bagi Anak ABK Tunarungu - Rosyid, Muhammad Amirudin; Fitrah, Putri Fauziatul; Nursangadah, Astuti; Tarbiburrohman, Farid; Alimi, Abdurrohman Wahid (Lembaga Yasin AlSys, 2022)
This study aims to 1). Showing how the characteristics of children with special needs are deaf, 2). Presenting various models of Islamic religious education guidance for children with special needs for the deaf. In this study using a qualitative method with a library approach. Islamic religious education is learning with various materials that discuss the religion of Islam. Like studying the Koran, Hadith, and so on. This becomes easier if done by children who do not have special needs. Unlike the case with children with special needs, they must require various methods to assist in studying each learning material, especially Islamic religious education. From this study, researchers found various rules and sources that were very relevant from various models of Islamic religious education guidance for children with special needs for the Deaf.